Quality of Life and Sexual Functioning of Women after Breast Cancer Surgery - Pačarić, Stana; Orkić, Želimir; Milostić-Srb, Andrea; Turk, Tajana; Farčić, Nikolina; Mikšić, Štefica; Adamčević, Silvia; Erić, Ivan; Gvozdanović, Zvjezdana; Srb, Nika (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Women with breast cancer can experience changes in sexual functioning and body images that can seriously affect their quality of life. AIM: The aim of this research was to study the quality of life and sexual functioning of women after a mastectomy and after a breast-conserving surgery and to compare post-operative quality of life. SUBJECTS AND METHODS: This cross-sectional study included 204 participants, 101 patients after a mastectomy and 103 patients after a quadrantectomy. The research was conducted using the Croatian version of the questionnaire of the European Organization for Research and Treatment of Breast Cancer, the questionnaire with the breast cancer module EORTC QLQ - BR 23. RESULTS: On the EORTC QLQ –BR23 scale, participants with mastectomy rated their sexual functioning (p < 0.001), sexual pleasure (p < 0.001), and systemic side effects (p = 0.04) lower comparing to women after breast-conserving surgery. The overall functionality scale was significantly lower (p = 0.03) for women who underwent mastectomy compared to those who underwent breast-conserving surgery. Participants under 51 years of age had worse body image 1 month after mastectomy (p = 0.006), while sexual functioning was better (p = 0.03) than in older age groups. In breast-conserving surgery group, 1 month after surgery, participants in the age group of 61 years and older assessed body image better (p = 0.04) than in the younger age group. Sexual functioning was rated better by women aged 51–60 years (p = 0.03). CONCLUSION: Results of this study show that women after breast conserving surgery have better quality of life, better sexual functioning and less side effects of systemic therapy compared to women after mastectomy. The type of surgery, patient’s age and time passed after completion of treatment are important factors which influence sexual functioning and quality of life in breast cancer survivors.